Post a New Question

algebra 2

posted by on .

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation.

x + y = 2
3x + 2y = 9

  • algebra 2 - ,

    x + y = 2 Multiply both sides by 2

    2 x + 2 y = 4

    2 y = 4 - 2 x



    3 x + 2 y = 9

    3 x + 4 - 2 x = 9

    x + 4 = 9

    x = 9 - 4 = 5


    x + y = 2

    5 + y = 2

    y = 2 - 5 = - 3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question